2012
DOI: 10.1289/ehp.1104049
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Nonaccidental and Cardiovascular Mortality in Relation to Long-term Exposure to Low Concentrations of Fine Particulate Matter: A Canadian National-Level Cohort Study

Abstract: Background: Few cohort studies have evaluated the risk of mortality associated with long-term exposure to fine particulate matter [≤ 2.5 μm in aerodynamic diameter (PM2.5)]. This is the first national-level cohort study to investigate these risks in Canada.Objective: We investigated the association between long-term exposure to ambient PM2.5 and cardiovascular mortality in nonimmigrant Canadian adults.Methods: We assigned estimates of exposure to ambient PM2.5 derived from satellite observations to a cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
398
11
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 541 publications
(451 citation statements)
references
References 24 publications
27
398
11
2
Order By: Relevance
“…Odds ratios using both the standard linear and threshold models were estimated for all ACS, STEMI, NSTEMI, UA, and NSTE‐ACS events for all patients and for patients with and without CAD. For comparison purposes, and consistent with reporting from various studies and reviews of the literature,1, 2, 3, 4, 5, 6, 7, 8, 11, 14, 15, 16 odds ratios associated with 10‐μg/m 3 incremental increases in PM 2.5 concentration are presented.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Odds ratios using both the standard linear and threshold models were estimated for all ACS, STEMI, NSTEMI, UA, and NSTE‐ACS events for all patients and for patients with and without CAD. For comparison purposes, and consistent with reporting from various studies and reviews of the literature,1, 2, 3, 4, 5, 6, 7, 8, 11, 14, 15, 16 odds ratios associated with 10‐μg/m 3 incremental increases in PM 2.5 concentration are presented.…”
Section: Methodsmentioning
confidence: 93%
“…Various prospective cohort studies of long‐term exposure (years or decades) have found that elevated PM 2.5 exposures are associated with increased risk of cardiovascular disease mortality3, 4, 5, 6, 7, 8, 9 and may contribute to the initiation and progression of related chronic diseases including atherosclerosis, hypertension, and diabetes 10, 11. The Global Burden of Disease 2010 analysis reported comparative burden of disease risk assessments from 67 risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Seinfeld and Pandis, 1988). These particles form smog and, in addition to being statistically associated with health impacts, such as bronchitis, asthma, cardiovascular disease and lung disease, cause premature deaths (Schwartz et al, 2002;Reiss et al, 2007;Pope et al, 2002Pope et al, , 2009Crouse et al, 2012). For example, there is a 6 and 8 % increase in the risk of cardiopulmonary and lung cancer mortality associated with exposure to 10 µg m −3 increases in PM 2.5 concentrations (Pope et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These two prospective cohort studies have undergone extensive reanalysis, replication, and extended analysis (5-7). Additional cohort studies have also been reported, and when evaluated in a meta-analytic review framework there is significant evidence that fine PM exposure contributes to risk of mortality (8)(9)(10).…”
mentioning
confidence: 99%